Another Generalized Closed Sets in Ideal Topological Spaces - O. Ravi; R. Asokan; A. Thiripuram (International Journal of Mathematics And its Applications, 2015)
Characterizations and properties of $\mathcal{I}_{gδ}$-closed sets and $\mathcal{I}_{gδ}$-open sets are given. A characterization of $δ$-$\star$-normal spaces is given in terms of $\mathcal{I}_{gδ}$-open sets.